2020
DOI: 10.1002/suco.202000052
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbon fiber on properties of concrete with different W/C and its air‐entraining models

Abstract: The addition of carbon fiber can change plain concrete (PC) to a quasi‐ductile material and improve its flexural properties through sharing the tensile stress transduced from concrete matrix. However, the influence rule and its mechanism of air entrained by carbon fiber on properties of concrete with different water to cement ratios (W/C) is not clear at present. Therefore, this research aims to explore this influence rule and mechanism. Eighteen kinds of concrete samples with W/C of 0.25, 0.3, and 0.45 includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…This effect can be attributable to fiber dosage in the concrete mix. Liu et al [60] analyzed the permeability of carbon fiber reinforced concrete and observed the same impact based on the watercement ratio. The fiber improves the impermeability of concrete only for the w/c ratio of 0.25.…”
Section: Discussionmentioning
confidence: 89%
“…This effect can be attributable to fiber dosage in the concrete mix. Liu et al [60] analyzed the permeability of carbon fiber reinforced concrete and observed the same impact based on the watercement ratio. The fiber improves the impermeability of concrete only for the w/c ratio of 0.25.…”
Section: Discussionmentioning
confidence: 89%